Supplementary speaking materials using task based language teaching for primary school in Yogyakarta context - Retno Baskoro Wulan (Journal of English Language and Pedagogy, 2019)
This research is aimed to develop supplementary speaking materials for fifth grade students. Belonging to educational research and development (R&D), this research employed a simplified six steps of Borg and Gall’s model (1983). The six steps are as follow (1) conducting needs analysis, (2) constructing course grid, (3) developing course grid based on the combination of the 2006 Curriculum (KTSP) and the result of the needs analysis for young learners. The English speaking material was designed based on the principles of Language Curriculum Design proposed by Nation & Macalister (2010) and task-based language teaching proposed by Willis (2003) (4) the tryout of the course grid to the fifth grade students at SD Kanisius Ganjuran Bantul, (5) evaluation and revision of course grid by the experts, and (6) final product. The finding shows that the product relies much on pertaining KD of the 2006 Curriculum and the teacher expected that the students need to improve speaking skill since they have opportunity to speak English. English speaking materials are in line with student’s wants who are young learners. The strengths of this product help students to improve their speaking skill especially the vocabularies, the language function used in spoken language. The tasks can fascinate the students on teaching and learning process of English lesson.